PENGARUH KOMPETENSI KOMUNIKASI, KECERDASAN EMOSIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI (STUDI PADA BADAN PENDAPATAN DAERAH KABUPATEN DAIRI) - Ferry V. Edward Sinurat; Wanry Barutu; Muhammad Arifin; Ramlan Bonarta Lumban Tobing; Sumardi Sihombing (Universitas Islam Islam Sumatera Utara, 2020)
The research is tittled “The Effect of Communication Competency, Emotional Intelegency and Organizational Culture towards Employee Performance Of Badan Pendapatan Daerah Kabupaten Dairi”. The objective would be to know the effect of Communication Competency, Emotional Intelegency and Organizational Culture towards Employee Performance Of Badan Pendapatan Daerah Kabupaten Dairi. Analysis method that use were descriptive analysis method and stastistic using multiple linear regression, simultaneous test and partial test. The calculation of data analysis was used SPSS software for Windows. The data that used were primer and secondary. This research were used the 47 respondents which determinate by simple random sampling. The result of this research by multiple linear regression test shows that the communication competency, emotional intelegency and organizational culture have positive and significant effect on employee performance Of Badan Pendapatan Daerah Kabupaten Dairi. And based on partial test showed that the organizational culture variable has dominant effect towards employee performance of Badan Pendapatan Daerah Kabupaten Dairi.